Influence of Reduced Saliva Production on Phonation in Patients With Ectodermal Dysplasia - Semmler, Marion; Kniesburges, Stefan; Pelka, Franziska; Ensthaler, Maria; Wendler, Olaf Dietrich; Schützenberger, Anne (Journal of Voice, 2021)
Objective: Patients with ectodermal dysplasia (ED) suffer from an inherited disorder in the development of the ectodermal structures. Besides the main symptoms, i.e. significantly reduced formation/expression of teeth, hair and sweat glands, a decreased saliva production is objectively accounted. In addition to difficulties with chewing/swallowing, ED patients frequently report on the subjective impression of rough and hoarse voices. A correlation between the reduced production of saliva and an affliction of the voice has not yet been investigated objectively for this rare disease. Methods: Following an established measurement protocol, a study has been conducted on 31 patients with ED and 47 controls (no ED, healthy voice). Additionally, the vocal fold oscillations were recorded by high-speed videoendoscopy (HSV@4 kHz). The glottal area waveform was determined by segmentation and objective glottal dynamic parameters were calculated. The generated acoustic signal was evaluated by objective and subjective measures. The individual impairment was documented by a standardized questionnaire (VHI). Additionally, the amount of generated saliva was measured for a defined period of time. Results: ED patients displayed a significantly reduced saliva production compared to the control group. Furthermore, the auditory-perceptual evaluation yielded significantly higher ratings for breathiness and hoarseness in the voices of male ED patients compared to male controls. The majority of male ED patients (67%) indicated at least minor impairment in the self-evaluation. Objective acoustic measures like Jitter and Shimmer confirmed the decreased acoustic quality in male ED patients, whereas none of the investigated HSV parameters showed significant differences between the test groups. Statistical analysis did not confirm a statistically significant correlation between reduced voice quality and amount of saliva. Conclusions: An objective impairment of the acoustic outcome was demonstrated for male ED patients. However, the vocal folds dynamics in HSV recordings seem unaffected.
CRIS-Team Scopus Importer:2021-08-13
Keywords: Ectodermal Dysplasia; Evidence-based Medicine; Saliva Production; Standardized Voice Evaluation